Photophobia or thermophobia in dry eye - A. Ebraheem (Российский офтальмологический журнал)
The sensory nerves that are accountable for the sensation of the cornea originate from the ophthalmic division of the trigeminal ganglion. Around 20% of the nociceptors present in the cornea serve a vital function in transmitting intense and sharp pain sensations when there is mechanical contact with the ocular surface. Roughly 70 percent of the nociceptors present in the cornea respond to different chemical stimuli, such as acetylcholine, prostaglandins, and bradykinin, as well as heat and mechanical irritants. The rest of the receptors are sensitive to temperature. Most of the patients who have cornea pathological conditions complain of photophobia as one of the clinical signs. Photophobia is characterized by an elevated sensitivity of the eye to light in contrast to its usual reaction. Given that light is composed of various wavelengths, each containing a certain amount of thermal radiation energy, the term “thermophobia” might be a more suitable descriptor than photophobia. This paper presents novel findings on the perception of photophobia in cornea inflammatory conditions. It thoroughly explores the proposed neural pathway of photophobia in various neurological and eye medical conditions, shedding light on the potential underlying causes for patients experiencing photophobia, even when the exact cause remains undetermined.